Nitrogen-neutrality: a step towards sustainability - Leip, Adrian; Leach, Allison; Musinguzi, Patrick; Tumwesigye, Trust; Olupot, Giregon; Tenywa, John Stephen; Mudiope, Joseph; Hutton, Olivia; Cordovil, Claudia M d S; Bekunda, Mateete (Environmental Research Letters, 2014)
We propose a novel indicator measuring one dimension of the sustainability of an entity in modern societies: Nitrogen-neutrality. N-neutrality strives to offset Nr releases an entity exerts on the environment from the release of reactive nitrogen (Nr) to the environment by reducing it and by offsetting the Nr releases elsewhere. N-neutrality also aims to increase awareness about the consequences of unintentional releases of nitrogen to the environment. N-neutrality is composed of two quantified elements: Nr released by an entity (e.g. on the basis of the N footprint) and Nr reduction from management and offset projects (N offset). It includes management strategies to reduce nitrogen losses before they occur (e.g., through energy conservation). Each of those elements faces specific challenges with regard to data availability and conceptual development. Impacts of Nr releases to the environment are manifold, and the impact profile of one unit of Nr release depends strongly on the compound released and the local susceptibility to Nr. As such, N-neutrality is more difficult to conceptualize and calculate than C-neutrality. We developed a workable conceptual framework for N-neutrality which was adapted for the 6th International Nitrogen Conference (N2013, Kampala, November 2013). Total N footprint of the surveyed meals at N2013 was 66 kg N. A total of US$ 3050 was collected from the participants and used to offset the conference's N footprint by supporting the UN Millennium Village cluster Ruhiira in South-Western Uganda. The concept needs further development in particular to better incorporate the spatio-temporal variability of impacts and to standardize the methods to quantify the required N offset to neutralize the Nr releases impact. Criteria for compensation projects need to be sharply defined to allow the development of a market for N offset certificates.